2012
DOI: 10.2174/138920112800784763
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Treatment Approaches in Schizophrenia Enhancing Neuroplasticity: Aerobic Exercise, Erythropoetin and Repetitive Transcranial Magnetic Stimulation

Abstract: Schizophrenia is a brain disorder associated with subtle, but replicable cerebral volume loss mostly prevalent in frontal and temporal brain regions. Post-mortem studies of the hippocampus point to a reduction of the neuropil constituting mainly of synapses associated with changes of molecules mediating plastic responses of neurons during development and learning. Derived from animal studies interventions to enhance neuroplasticity by inducing adult neurogenesis, synaptogenesis, angiogenesis and long-term pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 101 publications
0
11
0
1
Order By: Relevance
“…Research in noneating disorder populations has shown that some of these behaviors can significantly affect brain structure and function (Boraxbekk et al, 2015;Freund et al, 2012;Hadjikhani et al, 2015;Stice, Burger, & Yokum, 2013). Although exercise has the potential to increase brain volumes in old age, the opposite may be the case in young adults, and the amount of exercise also plays an important role (Williams et al, 2017;Wobrock, Hasan, & Falkai, 2012). For example, extreme exercise in ultramarathon runners was associated with reductions in temporal, occipito-parietal and anterior cingulate gray matter volumes, as well as reduced brain volume in the caudate nucleus (Freund et al, 2014); these alterations normalized on follow-up after 8 months.…”
Section: E F Fe Cts Of Exe Rc I Se H Yd Ra T Ion S T At U S Bi Nmentioning
confidence: 99%
“…Research in noneating disorder populations has shown that some of these behaviors can significantly affect brain structure and function (Boraxbekk et al, 2015;Freund et al, 2012;Hadjikhani et al, 2015;Stice, Burger, & Yokum, 2013). Although exercise has the potential to increase brain volumes in old age, the opposite may be the case in young adults, and the amount of exercise also plays an important role (Williams et al, 2017;Wobrock, Hasan, & Falkai, 2012). For example, extreme exercise in ultramarathon runners was associated with reductions in temporal, occipito-parietal and anterior cingulate gray matter volumes, as well as reduced brain volume in the caudate nucleus (Freund et al, 2014); these alterations normalized on follow-up after 8 months.…”
Section: E F Fe Cts Of Exe Rc I Se H Yd Ra T Ion S T At U S Bi Nmentioning
confidence: 99%
“…7 More recently, EPO effects have been expanded to neurodegenerative diseases, [8][9][10][11] multiple sclerosis, 12 and mood disorders. 13,14 Moreover, it has been demonstrated that EPO is critical for normal brain development. 15 This diversity in role seems to be supported by the fact that EPO upregulates intracellular molecular signaling pathways that include the anti-apoptotic and mitogen-activated protein kinase (MAPK) cascades among others.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, plasticity of the prefrontal cortex and subcortical interaction partners has been widely proposed to be central to the pathophysiology of various psychiatric disorders such as depression (Castren and Rantamaki, 2010;Lucassen et al), bipolar disorder (Kapczinski et al, 2008) and schizophrenia (Lewis, 2009). While this viewpoint is central to contemporary models on pathophysiology and treatment (Tamminga et al, 2012;Wobrock et al, 2012), neural plasticity has not always been at the forefront of thinking about the origins of schizophre-schizophrenia tends to manifest with the full clinical picture typically in late adolescence or early adulthood, signs of abnormal neural development are present much earlier and may be traced back to the second trimester of gestation (Piper et al, 2012;Powell, 2010). These data raise the question of why schizophrenia typically manifests during or after adolescence.…”
Section: Introductionmentioning
confidence: 99%